Effects of Acute and Chronic Exposure to Semicarbazide on the Sea Cucumber Apostichopus japonicus - Tian, Xiuhui; Li, Huanjun; Zhang, Xiuzhen; Xu, Yingjiang; Zhang, Huawei; Han, Dianfeng; Liu, Huan; Wang, Bin; Cui, Yanmei; Liu, Huihui; Zhou, Quanli; Gong, Xianghong (Frontiers in Environmental Science, 2021)
The effects of acute and chronic exposure to semicarbazide were carried out on the sea cucumber Apostichopus japonicus. A half-maximal lethal concentration of 3.72 g/L of semicarbazide hydrochloride (95% confidence interval 3.43-4.02 g/L) was deduced. At 20%, 4%, and 2% of the half-maximal lethal concentrations, a 28-day exposure induced morphological alterations, oxidative stress, and acetylcholinesterase (AChE) activity in the respiratory tree, intestinal tract, and longitudinal muscle of A. japonicus. Exposure to 20% of the half-maximal lethal concentration resulted in lesions in the respiratory tree and disintegration in the intestinal tract. Exposure to lower concentration induced a gradual accumulation of lesions in the respiratory tree, intestinal tract, and longitudinal muscle. Levels of markers of oxidative stress and neurotransmission, including superoxide dismutase (SOD), catalase, and AChE , were increased during the initial days of exposure and then decreased as response capacity reached saturation or was exhausted. The effects were most pronounced in A. japonicus exposed to 4%, followed by 20% and 2% of the half-maximal lethal concentration. At the later stages of the 28-day exposure, marker levels were decreased and close to levels in the control groups. Non-targeted metabolomics indicated that significantly different metabolites were screened out, 28 in the positive ion mode and 38 in the negative ion mode, impairments in neurological function, osmotic pressure regulation, energy metabolism, and protein digestion and absorption following exposure of A. japonicus to semicarbazide.